Analysis of The Influence of Digital Literacy, Government Policy, and Infrastructure on Coffee Productivity in Kerinci Regency - Syofya, Heppi; Haryadi, Haryadi; Junaidi, Junaidi; Hodijah, Siti (Universitas Negeri Gorontalo, 2024)
This study aims to analyze the influence of digital literacy, government policy, and infrastructure on coffee productivity in Kerinci Regency. A descriptive and explanatory research design was applied using a quantitative approach. The study population consisted of 117 registered coffee farmers, and a sample of 90 respondents was determined using the Slovin formula with a 5% margin of error. Data were collected through questionnaires, interviews, and field observations, complemented by secondary sources. The findings show that all three factors significantly affect coffee productivity. Digital literacy enables farmers to access agricultural information, adopt modern technologies, and expand market opportunities. Infrastructure improves efficiency by reducing production and distribution costs while enhancing connectivity. Among the factors, government policy has the strongest effect, particularly through training, certification, subsidies, and market promotion. These findings highlight that government policy, digital literacy, and infrastructure collectively play a crucial role in enhancing the productivity and competitiveness of coffee farmers.